Experimental Study on Effect of Mooring on Motion Response of Rounded-Shape FPSO Model - Siow, C. L.; Koto, J.; Yasukawa, H.; Matsuda, A.; Terada, D.; Guedes Soares, C.; Incecik, A.; Pauzi, M.; Maimun, A. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
This paper discusses the motions response of moored rounded-shape FPSO model due to the wave effect. The research analyzed the possibility of wave motion response of rounded-shape FPSO model affected by different mooring systems. Experiment of a scale FPSO model of 1:112 was conducted in basin tank at the National Research Institute of Fisheries Engineering, Japan. In the experiment, the FPSO model was firstly tested by attaching model scale of Catenary mooring lines to rounded-shape FPSO model. Then the experiment was repeated by attaching model scale of Taut mooring lines to the rounded-shape FPSO model. Comparing results obtained using Taut and Catenary mooring lines in regular wave were presented. This research concluded that the mooring systems would not give significant effect to wave frequency motion response of the rounded-shape FPSO.